Prosodic Patterns in Interaction of Low-Risk and at-Risk-of-Autism Spectrum Disorders Infants and Their Mothers at 12 and 18 Months. Issue 3 (2nd July 2016) - Quigley, Jean; McNally, Sinéad; Lawson, Sarah
ABSTRACT: Research has indicated differences in prosodic expression for infants-at-risk-of-autism spectrum disorders (ASD), and it has been proposed that caregiver speech to these infants may also be moderated prosodically. In typical development, the pitch range of maternal infant-directed speech (IDS) narrows and utterance intensity decreases with infant age, and similar patterns are evident in infant vocalizations. In this study, samples of English-speaking maternal and infant nonvegetative vocalizations produced during naturalistic interaction at ages 12 months and 18 months were analyzed to investigate this process in a group of infants-at-risk-of-ASD with their mothers and typically developing controls. Differences in the expression, developmental trajectory and synchrony of prosody were found for at-risk dyads compared with low-risk dyads. Possible explanations for these patterns and the implications for language development are explored.